2000
DOI: 10.1116/1.591427
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of twin defects in GaAs(111)B molecular beam epitaxy growth

Abstract: The formation of twin is common during GaAs(111) and GaN(0001) molecular beam epitaxy (MBE) metalorganic chemical vapor deposition growth. A stacking fault in the zinc-blende (ZB)(111) direction can be described as an insertion of one monolayer of wurtzite structure, sandwiched between two ZB structures that have been rotated 60° along the growth direction. GaAs(111)A/B MBE growth within typical growth temperature regimes is complicated by the formation of pyramidal structures and 60° rotated twins, which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 11 publications
2
16
0
Order By: Relevance
“…Interestingly, the faults become less prevalent in films grown under the Garich conditions that stabilize the ͱ 19ϫ ͱ 19 reconstruction. [13][14][15] A similar trend is found for the initial structures of GaAs nanowires grown by using masks ͑selective-area growth͒. 16 The reconstruction may thus be a key to controlling stacking faults in GaAs films and nanowires.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…Interestingly, the faults become less prevalent in films grown under the Garich conditions that stabilize the ͱ 19ϫ ͱ 19 reconstruction. [13][14][15] A similar trend is found for the initial structures of GaAs nanowires grown by using masks ͑selective-area growth͒. 16 The reconstruction may thus be a key to controlling stacking faults in GaAs films and nanowires.…”
supporting
confidence: 52%
“…This is qualitatively consistent with the experimentally observed trends. [13][14][15][16] Although this simple argument neglects detailed growth processes and the distinction between nanowires and films, it illustrates how the reconstruction may suppress stacking faults in GaAs.…”
mentioning
confidence: 99%
“…These relationships are the same as those between hexagonal and cubic structures that differ only in the stacking sequence of the close-packed planes. Due to the structural similarities [18] between the c-GaN (111) Conclusions In summary, the lateral overgrowth of both h-GaN and c-GaN films was successfully performed on stripe-patterned GaAs (001) substrates using SiO 2 mask as well as SiN x mask by MOVPE. The conventional TEM images and SAD patterns showed that h-GaN was considerably constructed along only (111) B facets in all samples, regardless of the different mask stripe orientations ([110] and [1 1 10] directions).…”
Section: Resultsmentioning
confidence: 99%
“…Also, the x=0.13 peak showed the mixed crystalline as well as a wide FWHM value. It suggests that this cause is related to the stacking faults due to the excess insertion of the cubic CdO (111) in the hexagonal ZnO (0002) at the growth temperature of 400 o C. Due to the structural similarity between the cubic (111) and hexagonal (0001) surfaces, the hexagonal ZnO can be easily reconstructed along the (111) facet of the cubic CdO with increasing the Cd flux [21]. Therefore, it is suggested that it can act as the cause of deterioration of the crystallinity of x=0.13 specimens.…”
Section: Resultsmentioning
confidence: 97%